Exclusive Personality - Radvilavičius, Vytautas (Problemos, 1998)
As the author's research adviser prof. E. Meškauskas was educated, intelligent, undogmatic critic; this thoughts were plain, easily understandable and well argued. He was strict adviser. In his lectures, publications there were formulated problems, methodoIogically consequent with logical deductions.